Antibacterial activity of polyphenolic fraction of Kombucha against Vibrio cholerae: targeting cell membrane. (18th January 2018) - Bhattacharya, D.; Ghosh, D.; Bhattacharya, S.; Sarkar, S.; Karmakar, P.; Koley, H.; Gachhui, R.
Abstract: The present study was undertaken to determine the mechanism of antibacterial activity of a polyphenolic fraction, composed of mainly catechin and isorhamnetin, previously isolated from Kombucha, a 14‐day fermented beverage of sugared black tea, against the enteropathogen Vibrio cholerae N16961. Bacterial growth was found to be seriously impaired by the polyphenolic fraction in a dose‐dependent manner. Scanning Electron Microscopy demonstrated morphological alterations in bacterial cells when exposed to the polyphenolic fraction in a concentration‐dependent manner. Permeabilization assays confirmed that the fraction disrupted bacterial membrane integrity in both time‐ and dose‐dependent manners, which were proportional to the production of intracellular reactive oxygen species (ROS). Furthermore, each of the polyphenols catechin and isorhamnetin showed the ability to permeate bacterial cell membranes by generating oxidative stress, thereby suggesting their role in the antibacterial potential of Kombucha. Thus, the basic mechanism of antibacterial activity of the Kombucha polyphenolic fraction against V. cholerae involved bacterial membrane permeabilization and morphological changes, which might be due to the generation of intracellular ROS. To the best of our knowledge, this is the first report on the investigation of antibacterial mechanism of Kombucha, which is mostly attributed to its polyphenolic content. Significance and Impact of the Study: The emergence of multidrug‐resistant Vibrio cholerae strains has hindered an efficient anti‐ Vibrio therapy. This study has demonstrated the membrane damage‐mediated antibacterial mechanism of Kombucha, a popular fermented beverage of sugared tea, which is mostly attributed to its polyphenolic content. This study also implies the exploitation of Kombucha as a potential new source of bioactive polyphenols against V. cholerae . Abstract : Significance and Impact of the Study: The emergence of multidrug‐resistant Vibrio cholerae strains has hindered an efficient anti‐ Vibrio therapy. This study has demonstrated the membrane damage‐mediated antibacterial mechanism of Kombucha, a popular fermented beverage of sugared tea, which is mostly attributed to its polyphenolic content. This study also implies the exploitation of Kombucha as a potential new source of bioactive polyphenols against V. cholerae .